LIGHTNING DEATH - A CASE REVIEW (Journal of Forensic Medicine & Toxicology, 2015)
Lightening strike is one of the most frequent causes of death by natural phenomena. Lightning strike results in damage to many systems, the cardiovascular and central nervous systems are usually the most drastically affected systems. It represents one of the leading causes of cardiac arrest and death from natural calamity. One third of lightning strike is fatal and in 70% of cases where the victims survive lands up with permanent sequelae. Various mechanisms of energy transfer to humans have been described. If death occurs immediately after a lightning strike the primary cause of death are usually cardiac arrhythmias. Other causes are central respiratory paralysis with secondary circulatory arrest and mechanical tears of internal organs are responsible for death.
Keywords: Lightning death; Direct strike; Contact voltage; Side splash; Ground strike